2019
DOI: 10.1111/tid.13047
|View full text |Cite
|
Sign up to set email alerts
|

Direct‐acting antiviral agents for liver transplant recipients with recurrent genotype 1 hepatitis C virus infection: Systematic review and meta‐analysis

Abstract: Background Comprehensive evaluation of safety and efficacy of different combinations of direct‐acting antivirals (DAAs) in liver transplant recipients with genotype 1 (GT1) hepatitis C virus (HCV) recurrence remains limited. Therefore, we performed this systematic review and meta‐analysis in order to evaluate the clinical outcome of DAA treatment in liver transplant patients with HCV GT1 recurrence. Methods Studies were included if they contained information of 12 weeks sustained virologic response (SVR12) aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“… 3 5 Several studies have demonstrated that DAA treatments are well tolerated in liver transplant patients and are successful at achieving sustained virologic response in more than 95% of patients. 6 Serious adverse events can occur, however, including rashes, cytopenia, allograft rejection, severe anemia, and mortality, but these were only reported in 4% of cases 7 and thus our case is an unusual presentation following DAA therapy. The exact pathogenesis is not fully understood but believed to share similar histological and clinical findings with classical AIH.…”
Section: Discussionmentioning
confidence: 76%
“… 3 5 Several studies have demonstrated that DAA treatments are well tolerated in liver transplant patients and are successful at achieving sustained virologic response in more than 95% of patients. 6 Serious adverse events can occur, however, including rashes, cytopenia, allograft rejection, severe anemia, and mortality, but these were only reported in 4% of cases 7 and thus our case is an unusual presentation following DAA therapy. The exact pathogenesis is not fully understood but believed to share similar histological and clinical findings with classical AIH.…”
Section: Discussionmentioning
confidence: 76%
“…reported in a systematic review involving 885 transplanted patients, all of the cases associated with genotype 1, with higher SVR rates (p < 0.01) in patients with METAVIR F0-F2 (SVR = 97%, 95% CI: 0.93-0.99), when compared to patients with F3-F4 (SVR = 85%, 95% CI: 0.79-0.90) 32 .…”
Section: Discussionmentioning
confidence: 94%
“…It is possible that the lower response rate was due to the predominance of genotype 3 two thirds of the cases), and more patients with advanced fibrosis (F4) being included. These two factors, genotype 3 and advanced fibrosis/cirrhosis are predictive of lower SVR in both transplanted and non-transplanted patients 31,32 .…”
Section: Discussionmentioning
confidence: 96%
“…In patients with cirrhosis, the rates of SVR ranged from 94% to 100% in the four treatment groups[30]. Several other clinical and real-world studies and meta-analyses have also reported the efficacy of this regimen in treating HCV GT1-infected patients, including: (1) Both treatment naïve and treatment-experienced patients[31-49]; (2) Patients with compensated cirrhosis or advanced liver disease[31,36,38,40,44-46,48,50-52]; and (3) Liver transplantation cases (the transplantation cases studied included treatment-naïve as well as treatment-experienced and those with cirrhosis and HCC prior to transplantation)[50,53-59]. The presence of fibrosis, cirrhosis, or HCC has been found to lower the SVR rates with sofosbuvir and ledipasvir combination in HCV GT1-infected patients in a few studies[56,58-62].…”
Section: Optimizing the Management Of Hcv Infectionmentioning
confidence: 99%